Pengaruh Bauran Promosi Terhadap Keputusan Pembelian Pegguna Tokopedia - Genira, Chika Felsia; Aisjah, Siti (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2023)
Technological development has brought along technological innovations such as the emergence of e-marketplaces and has changed people’s shopping behavior into online shopping. The fierce competition between those e-marketplaces requires a good implementation of promotional mix in order to increase customers’ purchasing decision. The objective of this research is to identify the influence of promotional mix, which consists of advertising, sales promotion, event and experiences, public relation and publicity, online and social media marketing, and mobile marketing on the purchasing decision of Tokopedia users in Malang. This explanatory research explains the causal relationships between its variables. The data of this research was harvested by distributing questionnaires to 120 people in Malang, who were selected using non-probability sampling method and purposive sampling with the criteria of Tokopedia users who live in the city with the minimum age of seventeen years and who have made any purchase from the e-marketplace. The results of the multiple linear regression analysis performed in SPSS version 29 have led to findings that event and experiences, public relation and publicity, online and social media marketing, and mobile marketing significantly influence the purchase decisions of Tokopedia users and that advertising and sales promotion do not significantly affect the purchase decision.   Abstrak Perkembangan teknologi menghadirkan inovasi teknologi berupa munculnya e-marketplace dan mengubah kebiasaan berbelanja menjadi secara online. Persaingan bisnis yang tinggi antar e-marketplace sehingga diperlukan implementasi bauran promosi yang baik untuk meningkatkan keputusan pembelian pelanggan. Penelitian ini bertujuan untuk mengetahui pengaruh dari bauran promosi yang terdiri dari advertising, sales promotion, event and experiences, public relation and publicity, online and social media marketing, dan mobile marketing terhadap keputusan pembelian pengguna Tokopedia di Malang. Jenis penelitian ini adalah eksplantori yang menjelaskan hubungan sebab akibat antar variabel. Penelitian ini menggunakan sampel sebanyak 120 responden dengan metode nonprobability sampling dengan teknik purposive sampling. Penyebaran kuesioner dilakukan di Malang. Sampel terdiri dari responden yang berdomisili di Malang, berusia diatas 17 tahun, dan pengguna Tokopedia yang sudah pernah melakukan pembelian. Analisis data menggunakan Analisis Regresi Linear Berganda dan uji hipotesis menggunakan uji F dan uji t yang diolah dengan SPSS ver.29. Hasil pengujian menunjukkan variabel event and experiences, public relation and publicity, online and social media marketing, dan mobile marketing memiliki pengaruh signifikan terhadap keputusan pembelian pengguna Tokopedia, sedangkan variabel advertising dan sales promotion tidak memiliki pengaruh signifikan terhadap keputusan pembelian pengguna Tokopedia.